2015
DOI: 10.1111/edt.12215
|View full text |Cite
|
Sign up to set email alerts
|

The use of pulse oximetry in evaluation of pulp vitality in immature permanent teeth

Abstract: Vital teeth provided consistent oxygen saturation readings, and non-vital teeth recorded no oxygen saturation values. During tooth development, the oxygen saturation values decreased. These findings confirm that the pulse oximetry is capable of detecting the pulpal blood flow and oxygen saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 16 publications
6
39
0
1
Order By: Relevance
“…No significant statistical correlation was found between the levels of body SaO 2 levels and heart rate on the patient's index finger and teeth (r=-0.02; p=0.85). This finding is in line with previous investigations (17,19,26).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…No significant statistical correlation was found between the levels of body SaO 2 levels and heart rate on the patient's index finger and teeth (r=-0.02; p=0.85). This finding is in line with previous investigations (17,19,26).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, 68 patients with a mean age of 26 years showed mean baseline pulp SaO 2 of 85.1% in maxillary central incisors. This result is in line with some previous studies (17,18) that showed similar pulp SaO 2 levels in this same tooth group. Conversely, in other investigations (18,19), pulp SaO 2 levels of 91.29% and 79.3% were reported.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mean baseline pulp SaO 2 level in this sample of 120 healthy maxillary central incisors was 84.76%. This value is higher than the 81.25% reported by Stella, et al 25 (2015) in an analysis of 110 maxillary central incisors, and similar to the 84.80% reported by Bargrizan, et al 26 (2016) in a sample of 190 healthy central incisors. Oxygen saturation values higher than those of this study (92.60%) were measured in maxillary incisors by Kataoka, et al 18 (2016).…”
Section: Discussionsupporting
confidence: 65%
“…Studies have reported variability according to different age ranges, such as from 9 to 14 years, 26 15 to 40 years, 16 , 19 , 25 15 to 55 years, 23 and 35 to 65 years. 20 In this study, participants aged 18 to 27 years were selected.…”
Section: Discussionmentioning
confidence: 99%